2014
DOI: 10.1097/spv.0000000000000075
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Anticholinergic Medications and Risk of Catheterization After Urogynecologic Surgery

Abstract: Higher exposure to perioperative anticholinergic medications increases the risk of a failed postoperative VT after outpatient urogynecologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…A separate study examining anticholinergic load in perioperative medications found that higher exposure to perioperative anticholinergic medications increased the risk of a failed postoperative VT following outpatient urogynecologic surgery. 36 ERAS protocols should be mindful of the perioperative anticholinergic load in patients undergoing benign gynecologic and urogynecologic surgeries in order to reduce the risk of postoperative voiding dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study examining anticholinergic load in perioperative medications found that higher exposure to perioperative anticholinergic medications increased the risk of a failed postoperative VT following outpatient urogynecologic surgery. 36 ERAS protocols should be mindful of the perioperative anticholinergic load in patients undergoing benign gynecologic and urogynecologic surgeries in order to reduce the risk of postoperative voiding dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Walter et al examined the effect of multiple anti-cholinergic medications on patients undergoing prolapse or anti-incontinence procedures. (31)…”
Section: Discussionmentioning
confidence: 99%
“…There was a low rate (5.2%) of PUR overall, and glycopyrrolate did not increase that risk 3 . Conversely, another retrospective review of 125 women undergoing pelvic reconstructive surgeries found that greater exposure to perioperative anticholinergic medications correlated with a higher risk of postoperative retention 19 …”
Section: Discussionmentioning
confidence: 93%